Antihyperglycemic Activity of Red Fruit Oil (Pandanus conoideus Lam) on Improving Kidney Function in STZ- NA-Induced Nephropathy Rats - Ayudia Cipta Khairani; Tri Wijayanti; Gunawan Pamudji Widodo (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2023)
Background: Type 2 diabetes mellitus can cause complications, one of which is diabetic nephropathy. Parameters that indicate damage to the kidneys are the increase in creatinine and albumin levels. One of the traditional medicines used in the treatment of DM is  red fruit (Pandanus conoideus Lam). Objective: The purpose of this study was to determine the antihyperglycemic activity and the effect of red fruit oil administration on creatinine levels, microalbumin, and renal histopathology in STZ-NA-induced rats. Methods: This study used 30 male Wistar rats conditioned with type 2 DM with STZ-NA induction. The rats have grouped into 6 groups: group I, the normal control, group II, the negative control, group III, the positive control (pioglitazone 15 mg/kg BW), and groups IV, V, and VI, the red fruit oil respectively 1.35 mL/kg BW,2.7 mL/kg BW, and 5.4 mL/kg BW. Red fruit oil is made in traditional way and prepared for 2 days. Parameters tested in the study include blood glucose levels, creatinine, microalbumin, and kidney histopathology. Data analysis used the ANOVA method followed by Tukey's post hoc test. Results: The results showed that a red fruit oil dose of 5.4 mL/kg BW was an effective dose in reducing blood glucose levels, microalbuminuria, and serum creatinine, and repairing damage to the kidneys of rats. The percent activity of a red fruit oil dose of 5.4 mL/kgBW for blood glucose levels, microalbuminuria and serum creatinine were 84.69%, 76.30%, and 92.20% respectively. Conclusion: Red fruit oil can reduce blood glucose levels, creatinine levels, microalbumin and can repair kidney damage.